2006
DOI: 10.1016/j.ydbio.2006.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and ectomesenchymal role of the type I TGF-β receptor ALK5 during facial morphogenesis and palatal fusion

Abstract: Transforming growth factor beta (TGF-beta) proteins play important roles in morphogenesis of many craniofacial tissues; however, detailed biological mechanisms of TGF-beta action, particularly in vivo, are still poorly understood. Here, we deleted the TGF-beta type I receptor gene Alk5 specifically in the embryonic ectodermal and neural crest cell lineages. Failure in signaling via this receptor, either in the epithelium or in the mesenchyme, caused severe craniofacial defects including cleft palate. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(173 citation statements)
references
References 95 publications
8
164
0
Order By: Relevance
“…Before palatal shelf elevation, epithelial expression of TGF-b1 and TGF-b3 is induced within the future adhesion site, and then diminishes during disintegration of the MES (Cui et al 1998;Cui and Shuler 2000;Yang and Kaartinen 2007;Bush and Jiang 2012). Global ablation of TGF-b2 or TGF-b3 ligands or cranial neural crest specific knockout of Tgfbr2 or Tgfbr1 causes cleft palate, highlighting the importance of this signaling pathway in palatogenesis (Kaartinen et al 1995;Proetzel et al 1995;Sanford et al 1997;Ito et al 2003;Dudas et al 2006;Xu et al 2006). In Tgfb3-null mutants, palatal shelf adhesion occurs, but impaired apoptosis causes persistence of the MES resulting in non-union of the palatal mesenchyme.…”
Section: Digit Malformations Caused By Disruption Of Tgf-b and Bmp Simentioning
confidence: 99%
See 1 more Smart Citation
“…Before palatal shelf elevation, epithelial expression of TGF-b1 and TGF-b3 is induced within the future adhesion site, and then diminishes during disintegration of the MES (Cui et al 1998;Cui and Shuler 2000;Yang and Kaartinen 2007;Bush and Jiang 2012). Global ablation of TGF-b2 or TGF-b3 ligands or cranial neural crest specific knockout of Tgfbr2 or Tgfbr1 causes cleft palate, highlighting the importance of this signaling pathway in palatogenesis (Kaartinen et al 1995;Proetzel et al 1995;Sanford et al 1997;Ito et al 2003;Dudas et al 2006;Xu et al 2006). In Tgfb3-null mutants, palatal shelf adhesion occurs, but impaired apoptosis causes persistence of the MES resulting in non-union of the palatal mesenchyme.…”
Section: Digit Malformations Caused By Disruption Of Tgf-b and Bmp Simentioning
confidence: 99%
“…In Tgfb3-null mutants, palatal shelf adhesion occurs, but impaired apoptosis causes persistence of the MES resulting in non-union of the palatal mesenchyme. Treatment of these mice with recombinant TGF-b3 or overexpression of Smad2 rescues palate fusion (Kaartinen et al 1997;Taya et al 1999;Cui et al 2005;Dudas et al 2006;Xu et al 2006). BMP signaling regulates specification and migration of cranial neural crest cells to the facial primordia (reviewed in Nie et al 2006), and also controls mesenchymal cell proliferation.…”
Section: Digit Malformations Caused By Disruption Of Tgf-b and Bmp Simentioning
confidence: 99%
“…These, in parallel with the transcription factors Snai1 and Snai2, promote MES apoptosis and disintegration. 6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups.…”
Section: Discussionmentioning
confidence: 64%
“…46) These TGF-β signaling pathways are crucially involved in the development and maintenance of various tissues, including vessels and craniofacial growth and patterning. Thus, mutations in Tgfbr1 and Tgfbr2 in mice caused craniofacial deformities such as cleft palate, 47,48) and craniofacial manifestations seen in LDS patients may reflect altered TGF-β signaling in neural crest derivatives. 49) Most mutations of TGFBR1 and TGFBR2 genes are missense substitutions of evolutionarily conserved residues that encode serine/threonine kinases, and have been verified in vitro and/or predicted to be associated with loss-of-function (LOF).…”
Section: Loeys-dietz Syndrome (Lds)mentioning
confidence: 99%